Messungen von dynamischen Tracern und Ozon in der arktischen Stratosphäre : Analyse und Interpretation flugzeuggetragener Submillimeterwellenmessungen - Bremer, Holger (Univ. Bremen, 2001)
Ozone chemistry, tracer measurements, radiometry, airborne,submillimeterwave, Arctic, stratosphere. - The Airborne Submillimeter Radiometer (ASUR) is a passive heterodyne instrument using a superconducting detector with an instrumental frequency range from 604.3 to 662.3 GHz.Operating onboard an aircraft to avoid absorption by tropospheric water vapor key species of the stratospheric ozone chemistry can be detected for a vertical altitude range from 15 to 55 km. In the winter 1999/2000 the ASUR instrument participated in the THESEO 2000/SOLVE project onboard the NASA research aircraft DC-8. Three deployments were carried ... : thesis